Pengaruh Propioseptive Neuromuscular Fascilitation (Pnf) Terhadap Kemampuan Aktivitas Fungsional Pada Post Stroke Tipe Spastik Di RSU. Haji Medan Tahun 2022 - Siem Teresia Simbolon; Trisno Susilo; Bibit tri Wahyudi (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Background: Stroke is a condition when the blood supply to the brain is interrupted due to a blockage (ischemic stroke) or rupture of a blood vessel (hemorrhagic stroke). This condition causes certain areas of the brain to not receive oxygen and nutrients, resulting in the death of brain cells. Factors for stroke due to high blood pressure, smoking, obesity, heart disease, genetics and high cholesterol. PNF is a stimulus with the desired reaction, which in the end will be achieved ability or coordinated movement. Purpose: This study was to determine the effect of Propioseptive neuromuscular facilitation on the ability of functional activity in post-stroke spastic type at Haji Medan General Hospital. Method: used in this research is experimental with one group pre test and post test design with purposive sampling technique with a sample of 15 people. The data were analyzed using the wilcoson test. Results: from the wilcoson test, 0.001 was obtained which was less than 0.005 (sig 0.000 <0.005) so that the hypothesis was decided that there was an effect of propioseptive neuromuscular facilitation on the ability of functional activities in post-stroke spastic type at RSU.Haji Medan. Conclusion: The result of this research is that there is an effect of Propioseptive neuromuscular facilitation on the ability of functional activity in post-stroke spastic type at RSU. Haji MedanKeywords : Stroke, PNF, Functional activity ability.